The evidence base for routine enquiry into adverse childhood experiences: A scoping review. (May 2019) - Ford, Kat; Hughes, Karen; Hardcastle, Katie; Di Lemma, Lisa C.G.; Davies, Alisha R.; Edwards, Sara; Bellis, Mark A.
Abstract: Background: Exposure to adverse childhood experiences (ACEs; e.g., maltreatment, household dysfunction) is associated with a multiplicity of negative outcomes throughout the life course. Consequently, increasing interest is being paid to the application of routine enquiry for ACEs to enable identification and direct interventions to mitigate their harms. Objective: To explore the evidence base for retrospective routine enquiry in adults for ACEs, including feasibility and acceptability amongst practitioners, service user acceptability and outcomes from implementation. Methods: A scoping review of the literature was conducted, drawing upon three databases (CINAHL, MEDLINE, PsycINFO) and manual searching and citation tracking. Searches included studies published from 1997 until end of April 2018 examining enquiry into ACEs, or the feasibility/acceptability of such enquiry across any setting. All included studies presented empirical findings, with studies focusing on screening for current adversities excluded. Results: Searches retrieved 380 articles, of which 15 met the eligibility criteria. A narrative approach to synthesize the data was utilized. Four studies examined practitioner feasibility and/or acceptability of enquiry, three reported service user acceptability and six studies implemented routine ACE enquiry (not mutually exclusive categories). Further, eight studies explored current practice and practitioner attitudes towards ACE enquiry. Conclusions: Limited literature was found providing evidence for outcomes from enquiry. No studies examined impacts on service user health or service utilization. Few studies explored feasibility or acceptability to inform the application of routine ACE enquiry. The implementation of routine ACE enquiry therefore needs careful consideration. Focus should remain on evaluating developing models of ACE enquiry to advance understanding of its impact.